Natural and anthropogenic disasters : vulnerability, preparedness, and mitigation - Jha, Madan Kumar (New Delhi : Capital Pub. Co., 2010)
Contributed articles.
Includes bibligraphical references and index.
Keywords: Disaster relief; Natural disasters; Emergency management; Disasters